Effects of Clonostachys rosea f. catenula Inoculum on the Composting of Cabbage Wastes and the Endophytic Activities of the Composted Material on Tomatoes and Red Spider Mite Infestation - Nomfusi Ntsobi; Morris Fanadzo; Marilize Le Roes-Hill; Felix Nchu (Microorganisms, 2021)
Globally, fungal inocula are being explored as agents for the optimization of composting processes. This research primarily evaluates the effects of inoculating organic vegetable heaps with the entomopathogenic fungus Clonostachys rosea f. catenula (Hypocreales) on the biophysicochemical properties of the end-product of composting. Six heaps of fresh cabbage (Brassica oleracea var. capitata) waste were inoculated with C. rosea f. catenula conidia and another six were not exposed to the fungus. The composted materials from the fungus- and control-treated heaps were subsequently used as a medium to cultivate tomatoes (Solanum lycopersicum). The biophysicochemical characteristics of the composted materials were also assessed after composting. In addition, the protective effect of the fungal inoculum against red spider mite (Tetranychus urticae) infestations in the tomatoes was evaluated through the determination of conidial colonization of the plant tissue and the number of plants infested by the insect. Furthermore, phytotoxicity tests were carried out post experiment. There were few significant variations (p < 0.05) in heap temperature or moisture level between treatments based on the weekly data. We found no significant differences in the levels of compost macronutrient and micronutrient constituents. Remarkably, the composted materials, when incorporated into a growth medium from fungus-treated heaps, induced a 100% endophytic tissue colonization in cultivated tomato plants. While fewer red spider mite infestations were observed in tomato plants grown in composted materials from fungus-treated heaps, the difference was not significant (χ2 = 0.96 and p = 0.32). The fungal treatment yielded composted materials that significantly (p < 0.05) enhanced tomato seed germination, and based on the phytotoxicity test, the composted samples from the heaps exposed to the C. rosea f. catenula inoculum were not toxic to tomato seeds and seedlings. In conclusion, this study showed that C. rosea f. catenula improved the quality of composted materials in terms of fungal endophytism and seed germination.